PELAKSANAAN PEMBELAJARAN PRA–VOKASIONAL UNTUK MENINGKATKAN PENGETAHUAN TENTANG DUNIA VOKASI PADA SISWA SMP TRIMULYA SEMARANG - Adelia Adjeng Aradhea; Fuad Abdillah; Nurul Burhan; Diana Langgeng Mustikawati (Journal of Vocational Education and Automotive Technology, 2025)
Pre-vocational learning is an effort made on children from an early age so that children are able to know and recognize the world of work as a direction for their future. The purpose of this study is to increase knowledge about the world of vocations in students through the implementation of pre-vocational learning which is carried out in collaboration with the subject teacher of Guidance and Counseling (BK) at Trimulya Junior High School, Semarang City. The data collection technique used in this study is to use instruments that are tested for validity in the form of pre – test and post – test. Subjects used in this study were students at Trimulya Junior High School Semarang. Based on the results of the research conducted, it can be concluded that there is an increase in knowledge about the vocational world in students at Trimulya Junior High School in Semarang City after the implementation of pre-vocational learning at Trimulya Junior High School in Semarang City.